2012
DOI: 10.1159/000336312
|View full text |Cite
|
Sign up to set email alerts
|

The Active Site Residue V266 of Chlamydial HtrA Is Critical for Substrate Binding during both in vitro and in vivo Conditions

Abstract: HtrA is a complex, multimeric chaperone and serine protease important for the virulence and survival of many bacteria. Chlamydia trachomatis is an obligate, intracellular bacterial pathogen that is responsible for severe disease pathology. C. trachomatis HtrA (CtHtrA) has been shown to be highly expressed in laboratory models of disease. In this study, molecular modelling of CtHtrA protein active site structure identified putative S1–S3 subsite residues I242, I265, and V266. These residues were altered by site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Plasmids, including empty pUT18C and pKNT25 and also positive control zip gene (encoding the leucine zipper GCN4 protein) containing plasmids were transformed into E. coli DHP‐1 with selection using kanamycin (50 μg ml −1 ) and ampicillin (100 μg ml −1 ) in Luria‐Bertani (LB) agar. From this point onwards antibiotics were always included when growing these strains and incubation was always carried out at 29°C (Gloeckl et al ., ). β‐Galactosidase activity on agar was examined following spotting of 10‐fold diluted E. coli overnight cultures grown in LB broth onto LB agar with IPTG (0.5 mM) and X‐gal (40 μg ml −1 ) and incubation for 16.5 h at 29°C.…”
Section: Methodsmentioning
confidence: 97%
“…Plasmids, including empty pUT18C and pKNT25 and also positive control zip gene (encoding the leucine zipper GCN4 protein) containing plasmids were transformed into E. coli DHP‐1 with selection using kanamycin (50 μg ml −1 ) and ampicillin (100 μg ml −1 ) in Luria‐Bertani (LB) agar. From this point onwards antibiotics were always included when growing these strains and incubation was always carried out at 29°C (Gloeckl et al ., ). β‐Galactosidase activity on agar was examined following spotting of 10‐fold diluted E. coli overnight cultures grown in LB broth onto LB agar with IPTG (0.5 mM) and X‐gal (40 μg ml −1 ) and incubation for 16.5 h at 29°C.…”
Section: Methodsmentioning
confidence: 97%
“…Whole body vibration (WBV) is a novel rehabilitative exercise that uses low amplitude, low frequency vibration administered through a platform or Power Plate. WBV shows potential as an effective therapeutic approach and has been studied in a variety of clinical settings that include rehabilitation of patients with chronic stroke [8], spinal cord injury [9], lumbar disk disease and lower back pain syndromes [10], Parkinson's disease [11], elderly with sarcopenia [12,13], chronic obstructive pulmonary disease (COPD) [14 ], multiple sclerosis [15], obesity, osteoporosis, osteoarthritis and fibromyalgia [16] and children with cerebral palsy [17]. A growing body of evidence in laboratory animals and patients with chronic stroke have shown that WBV reduces or reverses pathological remodeling of bone and such a treatment could also help reduce frailty related physiological deterioration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we used JO146 to evaluate the role of CtHtrA during heat stress and also during recovery from heat stress. We had previously shown increased protein levels of CtHtrA during a heat stress model, at 20 h PI, and this is also the phase of the developmental cycle at which we already know JO146 is effective (Huston et al, 2008; Gloeckl et al, 2012). C. trachomatis cultures (20 h PI) were heat stressed for 4 h in a 42°C 5% CO 2 incubator prior to subsequent restoration to 37°C and completion of the developmental cycle.…”
Section: Resultsmentioning
confidence: 75%